Current Organoid Culture Systems in Pancreatic Cancer - Liu, Lei; Sun, Jing; Chen, Sheng; Tang, Xuechan; Zhang, Shuai; Wang, Min; Yue, Qian; Zhong, Changqing; Li, Lianyong (Current Topics in Medicinal Chemistry, 2025)
Despite advances in therapeutic regimens, Pancreatic Cancer (PC) still remains an aggressive malignancy characterized by high treatment resistance, mortality, and poor clinical outcome. Hence, there is an urgent need for more effective therapeutic methods to improve the survival of PC patients. Currently, organoid culture systems have emerged as a preclinical research model for studying cancer progression, biology, and treatment responses, bridging the translational gap between in vivo and in vitro models. This review summarized the common culture systems of PC organoids, paving the way for precision medicine in PC.
Keywords: organoids